The discourse of freedom in post-revolution. Analysis of a 1977commemorative speech on April 25th - Ramos, Rui (2014)
This study draws on the conceptual framework and methodological tools of discourse analysis for the identification and description of the essential features of the Parliament President’s speech at the solemn parliamentary session commemorating April 25th 1974, on April 26th 1977 in the first session of the first legislature of the Parliament in democracy. The study focuses on the enunciative issues, the ethos of the enunciator and the most relevant isotopies that underlie his speech. We conclude that this discourse is constructed on a particularly marked personal vision, disclosing the set of values that his enunciator assumes as the builders of a new Portugal emerging from the revolution of April 25th 1974 and the commitments assumed before the Portuguese people.